Analisis Nilai Hambatan Jenis Aluminium Berdasarkan Panjang Kawat Yang Berbeda - Elisa Kasli; Via Risna Dewi; Hilda Mazlina (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aims to determine the value of aluminum specific resistance which is calculated based on Ohm's law. This research uses an experimental method. In this study, 4 experiments were carried out with different lengths of wire. The first experiment used a wire length of 0.05 m, the second experiment used a wire length of 0.1 m, the third experiment used a wire length of 0.15 m, and the fourth experiment used a wire length of 0.2 m. The results of the study showed that the wire length of 0.05 m obtained the value of the type resistance of 2.7 x 10-3 ÃÂ©m, the length of the wire of 0.1 m obtained the value of the type resistance of 2.7 x 10-3 ÃÂ©m, the length wire of 0.15 m obtained type resistance value of 2.7 x 10-3 ÃÂ©m and at a wire length of 0.2 m obtained type resistance value of 2.7 x 10-3 ÃÂ©m. Thus, it can be concluded that the change value of aluminum types will be the same value if the wire material used is also the same value.